Sucessão rural: a percepção dos agentes de ATER - Kestring , Karina (2021)
The rural young people have been leaving their properties even more seeking for better life conditions in the cities. In other hand, they can find these conditions in other rural properties. Therefore, this research aimed to analyses the behavior of these young people according to the perception of technical assistance and rural extension agents who develop their job in the West of Parana – BR region. To realize the research, it was contacted three institutions that have agents in the region: The Support and Promotion Center for Agroecology (CAPA), the Biolabore cooperative of professionals and the Parana Rural Development Institute (IDR – Parana). After, a questionnaire by Google Forms platform was sent for agents to answer. According to the answers, the rural young continue to leave the lands because they don’t feel that belong there, there is also a lack of dialogue with their parents, a gap of encouragement from parents who doesn’t giving young people freedom to work independently on the property and added in some cases the encouragement to become better life conditions out of there. It was concluded according to this study that the agents, even if indirectly, have covered this theme in their operation, but need more improvement seeking expand the conditions to young people continue in the land.